SOME WAYS OF TEACHING SPEAKING TO ELEMENTARY LEVEL LEARNERS - Bekbergenova Gulayim Ayjarikovna,; Tolibaeva Kamila Timurovna, (TADQIQOTLAR, 2026)
Abstract: Teaching speaking to elementary level learners is a foundational task in  any  English  language  curriculum.  At  this  stage,  learners  are  just  beginning  to communicate  using  simple  sentences,  basic  vocabulary,  and  everyday  expressions. Therefore, the main goals are to develop their confidence, help them use language in meaningful contexts, and lay the groundwork for more advanced communication in the future. One of the key principles in teaching speaking to beginners is the necessity of creating a safe, supportive, and motivating classroom environment. Learners at the elementary level are often hesitant to speak for fear of making mistakes. Encouraging positive attitudes towards mistakes as part of the learning process is essential. Teachers should praise attempts to speak, provide constructive feedback, and foster a classroom culture in which every student feels comfortable expressing themselves regardless of their proficiency.